Properties of cement sand brick containing fly ash as partial cement replacement - Norezzaty, Ahmad Nadzri (2019)
Fly ash can be found in large quantities because our country has several power plant stations. The waste disposal of fly ash effects to the environment surroundings. The cement production also causes air pollution, water pollution, and others. By using fly ash as an alternative construction material is a right step to preserve the environment. Hence, this study conducted to investigate the properties of cement sand brick containing fly ash as partial cement replacement. There are several tests conducted to investigate the effect of fly ash as partial cement replacement on compressive strength, flexural strength, and water absorption of cement sand brick. The test of brick specimens with replacement ratios of 0%, 10%, 20%, 30% and 40%, are measured and are compared with those of the bricks specimens without fly ash at the same ages. The water absorption measured at 28 days after the bricks undergo water curing. The type of curing used in the experiment is water curing in aged of 7 and 28 days. All experimented works are follow the standard of ASTM. Furthermore, the observation of strength behaviors are analyzed and discussing in terms of the properties of cement sand brick. In term of compressive strength, the higher the percentages of fly ash used, the lower the compressive strength of brick. With regard to flexural strength, the higher the percentages of fly ash, the lower the flexural strength of brick. Based on water absorption, the higher the percentages of fly ash, the higher the water absorption. Conclusively, the brick contain fly ash can be used for non-load bearing application.